2008
DOI: 10.1016/j.jcme.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cloth-covered chiropractic treatment tables as a source of allergens and pathogenic microbes

Abstract: Objective: Vinyl chiropractic tables have been found to harbor pathogenic bacteria, but wiping with a simple disinfection agent can significantly reduce the risk of bacteria. The aim of this study was to assess the presence of microbes and other allergens or pathogens on cloth chiropractic tables. Methods: Cloth-covered tables in a chiropractic college teaching clinic were selected. Samples were taken from the facial piece and hand rests with RODAC plates containing nutrient agar, followed by confirmatory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…11 The most recent study was conducted on cloth-covered chiropractic tables and found that these tables are a source of not only bacteria but allergens as well. 12 These studies highlight the need for infection control policies in chiropractic settings.…”
mentioning
confidence: 99%
“…11 The most recent study was conducted on cloth-covered chiropractic tables and found that these tables are a source of not only bacteria but allergens as well. 12 These studies highlight the need for infection control policies in chiropractic settings.…”
mentioning
confidence: 99%
“…Our literature search found 4 articles published on microbial analysis of chiropractic treatment table surfaces [5][6][7][8] ; 1 article on attitudes, beliefs, and current practices of students on hand hygiene and table sanitizing in chiropractic 13 ; and 1 poster presentation on the attitudes, beliefs, and current practices presented at the American Public Health Association's Conference in 2007. 14 In addition, one presentation at the 2008 Association of Chiropractic College's Research Agenda Conference was made on the topic of microbes on treatment tables along with a successful surveillance system and management effort to reduce risks.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were taken from all cloth-covered tables located in the clinic, which were limited to student and family use, using a Rodac plate (Becton, Dickinson, Sparks, MD) containing nutrient agar. 8 Confirmatory testing of specific cultures verified the presence of numerous allergens including the genus Candida, bacteria, and other general molds. Among the bacteria was S aureus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13 Investigations of treatment table surfaces in chiropractic teaching clinics have shown pathogenic microbes in multiple teaching clinics within the United States. [14][15][16][17][18] Attitudes and current practices of students and interns have been assessed in at least 2 teaching institutions with indications that additional education is needed. 19,20 In most cases, table sanitizing was reportedly not being performed because nothing was available with which to sanitize the table and no protocols or policies were in effect to guide such a process.…”
mentioning
confidence: 99%